Multi-layer refractory carbide
Patent Information
- Application Number
- JP2025050088
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-06
- Filing Date
- 2025-03-25
- Publication Date
- 2026-10-22
- Estimated Expiration
- 2041-08-05
Smart Images

Figure 0007940056000003 
Figure 0007940056000004 
Figure 0007940056000005
Abstract
Description
Technical Field
[0001] The present invention relates to a refractory carbide multilayer, a device comprising the multilayer, a CVD process for preparing the multilayer, and use of the multilayer.
Background Art
[0002] J. Lopez-Vidrier et al. (Materials Science and Engineering B 178(2013) pp. 639-644) describe silicon-rich silicon carbide (SRC) layers appropriately separated by SiC barrier layers. Crystalline Si or fused silica was used as the substrate. This multilayer was deposited by plasma-enhanced chemical vapor deposition (PECVD) using SiH₄, CH₄ and H₂ as gaseous precursors. Each SiC barrier layer had a thickness of 3 nm, and the SRC layer thickness was either 2, 3, or 4 nm. A 20 nm buffer layer of SiC was also deposited between the substrate and the multilayer. The SiH₄ flow rate was altered such that the excess Si concentration in the SRC layers was 20, 30, and 50 atomic percent, respectively.
[0003] EP 0 935 013 A1 describes a CVD-formed SiC product having low transmittance for light in a specific wavelength range. This CVD-formed SiC product is produced on a substrate by first depositing a SiC coating on the substrate by a CVD method, then removing the substrate, and forming at least one SiC layer having different particle characteristics either in the structure of the formed SiC product or on the surface thereof. This causes scattering, refraction, reflection and the like.
[0004] WO 2019 / 182306 A1 describes a graphite coating method and a hybrid coating method that includes: a) supporting solid silicon on a porous support; b) preparing a first silicon carbide coating layer by placing a graphite substrate and the porous support supporting solid silicon in a vacuum chamber and then heat-treating it at 1,400 to 2,000°C; and c) depositing a second silicon carbide coating layer on the first silicon carbide coating layer by chemical vapor deposition. Research has been conducted to avoid cracks that occur in conventional SiC coatings during the cooling process after vapor deposition in this method.
[0005] EP 3 514 130 A1 describes a silicon carbide coated article (or article) comprising IA) a porous graphite substrate, II-A) at least two SiC coating layers of different densities, and optionally III-A) an interface layer located between the graphite substrate and the SiC coating layers, the interface layer comprising porous graphite and pores filled with SiC in the form of tendrils at least 50 μm long, extending from at least one of the SiC coating layers to the porous graphite substrate. The document further states that in such a multilayer SiC coated article, at least two SiC coating layers II-A) may be characterized by different crystal sizes.
[0006] U.S. Patent No. 10,294,163 B2 relates to a SiC-coated carbon composite material comprising a graphite substrate and a CVD-SiC coating covering the graphite substrate. The SiC-impregnated layer extends from the CVD-SiC coating and is contained around the core. The SiC-impregnated layer consists of multiple regions arranged such that the Si content decreases progressively from a first surface on the CVD-SiC coating side to a second surface on the graphite substrate side.
[0007] While WO 2019 / 182306 A1, EP 3 514 130 A1, and U.S. Patent No. 10,294, 163 B2 focus on how SiC coatings provide better adhesion to graphite substrates, little attention has been paid to improving the integrity of the carbide coating itself. Coating substrates with ceramics by CVD is a common method for extending the life of graphite substrates, especially when used in high-temperature and corrosive / oxidizing environments. Nevertheless, ceramics are subject to degradation. Degradation pathways include, for example, microcracks in the film that propagate into the substrate over time, thereby exposing the substrate to irritating chemicals, often leading to premature etching and physical decomposition of the substrate. Refractory carbide coatings of graphite are particularly susceptible to such degradation. The use of intermediate layers between carbide and graphite, already proposed in the prior art, can only mitigate these problems to a certain extent. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] EP 0 935 013 A1 [Patent Document 2] WO 2019 / 182306 A1 [Patent Document 3] EP 3 514 130 A1 [Patent Document 4] US Patent No. 10,294,163 B2 [Non-patent literature]
[0009] [Non-Patent Document 1] Materials Science and Engineering B 178(2013) pp.639-644 [Overview of the project] [Problems that the invention aims to solve]
[0010] The fundamental problem of this invention is to provide a constituent material for high-temperature applications that can be used for extended periods under conditions involving mechanical (and possibly mechanical due to temperature gradients) stress and exposure to thermal etching gases, is very readily available, and has precisely controlled emissivity. [Means for solving the problem]
[0011] The inventors have discovered that a solution to this problem can be provided by designing the structure of the refractory carbide coating itself. This problem concerns a multilayer refractory carbide structure comprising a first layer, a second layer, and a third layer, The first layer has an average thickness of at least 25 nm and contains at least one type of refractory carbide. The second layer has an average thickness of at least 25 nm and contains at least one type of refractory carbide. The third layer has an average thickness of at least 25 nm and contains at least one type of refractory carbide. The first layer is solved by a multilayer structure with a larger average linear intersection grain size than the second layer. [Brief explanation of the drawing]
[0012] [Figure 1] This shows a magnified schematic diagram of the cross-section of a device for high-temperature applications. [Figure 2] This shows a magnified schematic diagram of the cross-section of a device for high-temperature applications. [Figure 3] This shows a magnified schematic diagram of the cross-section of a device for high-temperature applications. [Figure 4] Enlarged schematic diagrams of the cross-sections of the devices for high-temperature applications according to Examples 1a, 1b, and 1c are shown. [Figure 5] This shows a cross-sectional scanning electron microscope (SEM) image of the device of the present invention, including the multilayer formed by Example 1a. [Figure 6] Examples 1a (left SEM image), 1b (center SEM image), and 1c (right SEM image) show SEM images of the multilayer device of the present invention having six layers formed by these examples. [Figure 7] The bottommost graph shows the X-ray diffractogram (XRD) of a sample coated with a silicon carbide layer containing a single large silicon carbide crystal. The topmost graph shows the X-ray diffractogram of a sample coated with a single silicon-rich silicon carbide layer. The second, third, and fourth diffractograms from the top correspond to Sample 1a, Sample 1b, and Sample 1c, respectively. [Figure 8] Shows an EDXS line scan measured on a cross-section of the illustrated multilayer comprising 6 layers. [Figure 9] Shows cross-sectional SEM images of the multilayer comprising 6 layers before (left) and after (right) etching in HCl gas at 1300°C. [Figure 9A] Shows a single SiC layer deposited on a graphite substrate. [Figure 10] Shows an enlarged schematic cross-sectional view, an SEM image, and an EDXS line scan of a device for high-temperature applications according to Example 2. [Figure 11] Shows cross-sectional SEM images of the multilayer according to Example 2 before (left) and after (right) etching in HCl gas at 1300°C. [Figure 12] Shows an enlarged schematic cross-sectional view of a device for high-temperature applications according to Example 3. [Figure 13] Shows an SEM cross-sectional image of the device according to Example 3. [Figure 14] Shows cross-sectional SEM images of the multilayer according to Example 3 before (left) and after (right) etching in HCl gas at 1300°C. [Figure 15] The average linear intercept surface grain size (vertical axis) is plotted against the total layer thickness (horizontal axis). The data obtained for the comparative silicon carbide monolayer is represented by black circles. The data obtained for the silicon carbide multilayer of the present invention is represented by black triangles (samples from Example 1a), black squares (samples from Example 2), and black diamonds (samples from Example 3). [Figure 16] Shows an SEM image of a polished cross-section, in which a sample of the single-layer coating deposited under the conditions referred to as "porous layers 12 and 14" in Example 3 was fractured, and the cross-section was gently polished first using a diamond polishing disk and then using a diamond slurry. [Modes for carrying out the invention]
[0013] The multilayer may be an independent multilayer or a multilayer on a part of the surface of a device. An independent multilayer does not include a substrate. Neither of the two main surfaces of an independent multilayer is attached to a substrate. Thus, the present invention further relates to a device for high-temperature applications that includes the multilayer of the present invention on the surface of the material of the device. The high temperature described herein typically means a temperature in the range of 200 to 4000°C, preferably 300 to 3000°C, for example, 400 to 2500°C.
[0014] The material of the device is not limited. All materials that are stable at high temperatures for high-temperature applications are suitable as the material of the device. Preferably, the material of the device includes graphite or elemental silicon. The material of the device may be, for example, a graphite material, a carbon fiber reinforced material, or elemental silicon. Elemental silicon is preferably in the form of a wafer, as is used, for example, in the semiconductor industry. The material may have the shape of a support for semiconductor applications. Such supports for semiconductor applications (wafer supports) often have the shape of a disk or a barrel with inclined sidewalls, each having one or more recesses for arranging a semiconductor substrate, such as a silicon-based wafer, to be processed on the support, and it is well known in the art that such supports are processed in an epitaxy reactor or MOCVD reactor, or a plasma etching reactor such as a focusing ring, or an RTP reactor, i.e., an RTP ring, which are conventionally used to grow layers on wafers. However, the invention of multilayers on the surface of the material of the device does not preclude the presence of another layer between the graphite material and the multilayer. Such other layers would also form the material of the device.
[0015] Therefore, the constituent materials referred to herein may be multilayers themselves or devices. In this specification, the term “multilayer” means multilayers, whether or not they are part of a device. Whenever various specific multilayer features or properties are discussed, they are explicitly referred to in terms of independent multilayers and, on the other hand, multilayers of devices.
[0016] Refractory carbides are well known to those skilled in the art of general surface coatings or chemical vapor deposition (CVD). Refractory carbides contain non-carbon carbide constituent materials and carbon. In silicon carbide, for example, the non-carbon carbide constituent material is silicon. The present invention is not limited to specific refractory carbides, and several refractory carbides may be preferred depending on the specific application to which the multilayer of the present invention is applied. The refractory carbide contained in one of the first, second, third (and any other available) layers may be the same as or different from the refractory carbide contained in any other of the first, second, third (and any other available) layers.
[0017] A refractory carbide contained in one layer and a refractory carbide contained in any other layer are considered "the same" if both refractory carbides contain the same non-carbon carbide constituent material (e.g., silicon). The layers, however, may differ in respect to, for example, the average linear section grain size, porosity, or the content of non-carbon constituents.
[0018] A refractory carbide contained in one layer is considered "different" from a refractory carbide contained in any other layer if both refractory carbides contain different non-carbon carbide constituent materials.
[0019] Preferably, at least one refractory carbide of at least one layer contains silicon carbide, tantalum carbide, niobium carbide, hafnium carbide, tungsten carbide, boron carbide, niobium tantalum carbide, hafnium tantalum carbide, or hafnium niobium carbide.
[0020] More preferably, the first, second, and third layers each contain the same refractory carbide selected from silicon carbide, tantalum carbide, niobium carbide, hafnium carbide, tungsten carbide, boron carbide, niobium tantalum carbide, hafnium tantalum carbide, or hafnium niobium carbide, particularly the same refractory carbide selected from silicon carbide, tantalum carbide, niobium carbide, and hafnium carbide. Most preferably, the first, second, and third layers each contain silicon carbide.
[0021] Regardless of the specific context, the term “refractory carbide” in this specification preferably means “silicon carbide.” While specific effects have been shown for silicon carbide in particular, the growth of other refractory carbides in CVD follows the same or similar physical principles as shown in the examples, so it is reasonable to assume that the same or similar effects will be observed for other refractory carbides as well.
[0022] According to the present invention, the refractory carbide multilayer comprises a first layer, a second layer, and a third layer. Each of these layers contains refractory carbide. As can be seen from the various figures herein, the number of layers can be very easily recognized from SEM images. The number of refractory carbide-containing layers may be much greater than 3. The multilayer may include, for example, 3 to 1000 refractory carbide-containing layers, 3 to 100 refractory carbide-containing layers, or, for example, 4 to 50 refractory carbide-containing layers. The number of refractory carbide-containing layers may preferably be 3 to 12, for example 3 to 10 (or particularly 4 to 12, for example 4 to 10).
[0023] The present invention does not exclude other layers, i.e., layers that do not contain refractory carbides. The multilayer may include, for example, one carbon layer or more carbon layers. In this specification, “carbon layer” preferably means “pyrolytic carbon layer.” Any carbon layer may be located anywhere in the multilayer. This means that the multilayer may include a pyrolytic carbon layer sandwiched between refractory carbide-containing layers. The pyrolytic carbon layer may be the outermost layer. In a device, the pyrolytic carbon layer may be sandwiched between the innermost refractory carbide-containing layer and the device material.
[0024] In this specification, the term “average thickness” means the thickness determined from SEM cross-sectional images produced by cutting or breaking a multilayer (or the material thereof, if the multilayer is part of a device). Layers can be distinguished in the SEM cross-sectional image by their appearance, such as light-dark contrast, grain size, morphology, or porosity. The thickness of an individual layer can be determined by measuring the distance between the lower and upper boundaries of the layer along at least five lines running perpendicular to the multilayer surface. These lines are placed at various locations, and the thickness of the layer must represent a majority of the entire layer. The layer thickness is the average of the measurements at each line.
[0025] According to the present invention, the first layer has an average thickness of at least 25 nm, preferably at least 100 nm, for example, at least 1 μm. The average thickness of the first layer can be very large, as the deposition process can be continued until a very thick layer is formed. The average thickness of the first layer in an independent multilayer is usually not greater than 5 mm. In the device of the present invention, the first layer is usually thin. If the multilayer of the present invention is on the surface of a material, the strength of the material prevents cracking even in a very thin multilayer—and the individual layers contained within it. The (multi)layer is stabilized by the material. The average thickness of the first layer included in the multilayer of the device according to the present invention may be, for example, in the range of 25 nm to 200 μm, preferably in the range of 100 nm to 180 μm, and particularly in the range of 1 μm to 160 μm. In an independent multilayer of the present invention, the first layer is usually much thicker. The average thickness of the first layer included in an independent multilayer according to the present invention may be, for example, in the range of 0.25 μm to 5 mm, preferably in the range of 1 μm to 3 mm, and particularly in the range of 10 μm to 2 mm.
[0026] The same considerations apply to the second and third layers.
[0027] The average thickness of the second layer included in the multilayer of the device according to the present invention may be, for example, in the range of 25 nm to 200 μm, preferably in the range of 100 nm to 180 μm, and particularly in the range of 1 μm to 160 μm. The average thickness of the second layer included in the independent multilayer according to the present invention may be, for example, in the range of 0.25 μm to 5 mm, preferably in the range of 1 μm to 3 mm, and particularly in the range of 10 μm to 2 mm.
[0028] The average thickness of the third layer included in the multilayer of the device according to the present invention may be, for example, in the range of 25 nm to 200 μm, preferably in the range of 100 nm to 180 μm, and particularly in the range of 1 μm to 160 μm. The average thickness of the third layer included in the independent multilayer according to the present invention may be, for example, in the range of 0.25 μm to 5 mm, preferably in the range of 1 μm to 3 mm, and particularly in the range of 10 μm to 2 mm.
[0029] The average thickness of all individual layers is preferably in the range of 0.025 μm to 500 μm, most preferably 0.05 μm to 250 μm, particularly 0.1 μm to 200 μm, for example, 0.2 μm to 150 μm, for all layers that are multilayer layers of the device. The average thickness of all individual layers is preferably in the range of 0.1 μm to 100 mm, most preferably 0.2 μm to 50 mm, particularly 0.3 μm to 10 mm, for example, 0.4 μm to 5 mm, for all layers that are independent multilayer layers. The preferred effect of the layers is that they are more consistent when the average thickness of each layer increases a certain minimum value. The top of the individual particles in the lower layer can affect the crystal growth of the outer layer, even through a very thin intermediate layer. Beyond the upper limit of the thickness range, coating becomes very time-consuming. This makes the coating method very expensive, and the material or component on which the layers are deposited may bend due to mechanical stress, which can also be caused by a mismatch in thermal expansion between the layer and the coated material.
[0030] When the multilayer is a multilayer of a device, the average thickness of the multilayer is preferably in the range of 1 μm to 1 mm. This ensures reliable protection of the multilayer-coated material with a reasonable deposition time and therefore a reasonable cost. When the multilayer is an independent multilayer, the average thickness of the multilayer is preferably in the range of 100 μm to 100 mm.
[0031] According to the present invention, the first layer has a larger average linear section grain size than the second layer. This more quantitatively expresses that the first layer generally contains larger crystals than the second layer. The average linear section grain size of the layer can be determined from the cross section in an electron microscope image by counting the number of grain boundaries on a line that crosses at least 20 grain boundaries at half the thickness of the layer. The average linear section grain size is calculated by dividing the length of the line by the number of grain boundaries on that line, which is similar to the definition of "average linear section grain size" in ISO 13383-1:2012(EN).
[0032] As the inventors have discovered, the crystal size can be controlled very flexibly and easily by modifying the CVD coating conditions. Pores that appear to hinder the growth of refractory carbide crystals have been found to form under certain conditions, which are described in relation to Example 3 below. Other conditions appear to aid in the deposition of elemental silicon and hinder the growth of refractory carbide crystals. Thus, various possibilities exist to ensure that the refractory carbide crystals in one layer grow larger than those in another layer. This results in a multilayer in which the mean linear section grain size of the first layer is larger than that of the second layer. The present invention does not require any other differences between the first and second layers other than the mean linear section grain size. However, the present invention does not exclude other differences between the first and second layers other than the mean linear section grain size, as described below.
[0033] The second layer may contain, for example, more non-carbon components (e.g., silicon) of the refractory carbide (e.g., silicon carbide) than the first layer. If the refractory carbide contained in the second layer is silicon carbide, the second layer may contain, for example, more silicon than the first layer. Surprisingly, this has been found to prevent the formation of deep etch pits shown in Figures 2 and 9A, thus providing an additional protective mechanism for the multilayer device. The inventors further hypothesize that the toughness of the multilayer increases because the silicon-rich layer is more deformable (Young's modulus / hardness decreases) and relieves stress. It also makes it possible to adjust the crystal diameter (i.e., surface grain size) of the outer surface of the multilayer when the outermost layer of a defined thickness is deposited on such a second layer, as will be discussed below with reference to Figure 15.
[0034] Elemental silicon can be detected by XRD in multilayer structures. If silicon is not present in the outermost layer and the outermost layer is thick, the multilayer coating can be removed in stages, and XRD can be applied after each removal. The penetration depth of the XRD is approximately 30-50 μm. The Si-to-C atomic ratio can be determined by EDXS, XPS, or TOF-SIMS measurement, and may be in the range of, for example, 1.01:1 to 10:1, preferably 1.03:1 to 4:1, or for example, 1.1:1 to 2:1.
[0035] The porosity of the second layer may exceed that of the first layer. This allows for crack deflection and increased etching resistance, which ensures the long-term use of the constituent material (i.e., devices or multilayers) in high-temperature and / or corrosive environments. Porosity, as defined herein as the volume fraction of pores within a layer, can be measured from SEM images. For this purpose, cross-sections of the coating are prepared by cutting and gentle polishing, fracture and gentle polishing, or focused ion beam (FIB) method. In the cross-section, pores and solid refractory carbides can be distinguished by light-dark contrast. The area of the cross-section covered by pores is measured for each layer and divided by the total area examined to obtain the area fraction of pores.
[0036] Assuming that pores are uniformly distributed throughout the entire volume of the coating, the area fraction of pores is equal to the porosity defined above. The porosity of the second layer may be, for example, 0.05 to 30%, preferably 0.1 to 20%, and most preferably 0.15 to 10%. If the porosity is higher, the layer density is lower, and vice versa. As with porosity, the layer density is also determined from SEM image analysis.
[0037] In a multilayer structure, the second layer may be sandwiched between the first and third layers. Furthermore, the third layer may have a larger average linear section grain size than the second layer. This combines the generally good hardness / density of the two layers (first and third) containing larger refractory carbide crystals (or having larger average linear section grain sizes) with protection against deep etch pit formation and mechanical failure throughout the coating. Thus, it is also possible to adjust the surface crystal diameter (i.e., surface grain size) by selecting the thickness of the outermost layer.
[0038] In a multilayer structure, the first layer may be sandwiched between the second and third layers. Furthermore, the first layer may have a larger average linear section grain size than the third layer, i.e., the first layer may have a larger average linear section grain size than both the second and third layers. This combines the generally good hardness / density of one (first) layer containing larger refractory carbide crystals (or having a larger average linear section grain size) with protection against deep etch pit formation and mechanical failure throughout the coating. Thus, by selecting the thickness of the fourth outermost layer, it is also possible to deposit a fourth outermost layer with a controlled surface crystal diameter (i.e., surface grain size).
[0039] In other alternative multilayer configurations, the second layer may contain more non-carbon components (e.g., silicon) of the refractory carbide (e.g., silicon carbide) than the first layer, and the porosity of the third layer may exceed that of the first layer. In these alternative multilayer configurations, if the refractory carbide is silicon carbide, the second layer may contain more silicon than the first layer, and the porosity of the third layer may exceed that of the first layer. This increases etching resistance, increases mechanical stability, and provides an adjustable crystal size (i.e., surface grain size).
[0040] In a preferred multilayer structure, the average thickness of the first layer is greater than the average thickness of the second layer. The inventors do not assume that the desirable effects provided by the second layer increase linearly with respect to the thickness of the second layer when the second layer is considerably thicker. Therefore, for a given total multilayer thickness, it is advantageous to instead increase the thickness of the first layer, which has a larger average linear intersection grain size and is more robust.
[0041] A preferred multilayer is one in which the average linear intercept surface grain size is 0.1 to 50 μm, more preferably 0.2 to 40 μm, most preferably 0.3 to 30 μm, and particularly preferably 0.4 to 20 μm, for example, in the range of 0.5 to 10 μm. The average linear intercept surface grain size is measured according to the definition of "average linear intercept grain size" in ISO 13383-1:2012(EN). The technical effect related to surface grain size is that the larger the surface grain size, the shorter the overall surface grain boundary length.
[0042] Nevertheless, surprisingly, etching damage was observed to be more prevalent.
[0043] Therefore, a smaller surface particle size is preferred.
[0044] The present invention further relates to a CVD method for preparing a multilayer according to the present invention, in which a refractory carbide layer is formed that contains more or less non-carbon components (e.g., silicon) of the refractory carbide (e.g., silicon carbide) than adjacent layers, and / or a refractory carbide layer having a different porosity from adjacent layers. The refractory carbide layer containing more or less non-carbon components (e.g., silicon) of the refractory carbide (e.g., silicon carbide) than adjacent layers, and / or a refractory carbide layer having a different porosity from adjacent layers is preferably applied in a preceding or succeeding layer formation step. Atmosphere composition, pressure, and / or Temperature of the CVD coating atmosphere This is different from the conditions (for example, condition B). Atmosphere composition, pressure, and / or Temperature of the CVD coating atmosphere The layers are deposited under the conditions (e.g., condition A). According to the preferred method of the present invention, a multilayer of three or more layers is formed by periodically changing conditions A and B. If a multilayer containing two or more different types of layers is desired, conditions A and B are different. Atmosphere composition, pressure, and / or Temperature of the CVD coating atmosphere It is possible to deposit further layers under certain conditions (e.g., condition C).
[0045] Preferably, the CVD method of the present invention includes thermal CVD. Thermal CVD is different from plasma-enhanced chemical deposition (PECVD). Thermal CVD typically requires much higher temperatures than PECVD but does not require a plasma source. In this specification, the expression "thermal CVD" means CVD at a temperature of at least 800°C. A particularly preferred CVD method of the present invention is thermal CVD, in which the entire multilayer is deposited at a temperature of 800°C or higher.
[0046] A refractory carbide layer having a different porosity from the adjacent layer can be created, for example, by changing the content of the carbon source, such as CH4, C2H2, C2H4, C2H6, C3H6, C3H8, C4H8, or C4H in a CVD coating atmosphere. 10 By varying the content of the carbon source selected, deposition can be performed from a CVD coating atmosphere.
[0047] According to a preferred method of the present invention, - A refractory carbide layer containing more or less non-carbon components (e.g., silicon) of refractory carbides (e.g., silicon carbide) than adjacent layers, or - A refractory carbide layer with a different porosity than the adjacent layer. A layer is formed thereon, and a layer with a larger average linear section cross-sectional grain size is deposited thereon, and the deposition of the layer with a larger average linear section cross-sectional grain size continues until the outer surface of the layer with a larger average linear section cross-sectional grain size reaches a predetermined average linear section surface grain size.
[0048] The present invention further relates to a multilayer or device obtained by the method of the present invention.
[0049] Another aspect of the present invention is the use of the multilayer of the present invention as a coating for a support to extend the life of the support in an etching gas-containing atmosphere and / or when exposed to mechanical stress. As described above, the support is preferably a support for semiconductor applications. The etching gas may contain, for example, HCl, NH3, H2, N2, halogens, gallium, aluminum, arsenic, Al(CH3)3, or silane. Although the inventors have demonstrated the high resistance of the multilayer of the present invention to etching with HCl, it is thought that the same or similar effects may be observed with other gases. This is because the precise nature of the boundaries or gaps between particles appears to control the etching process, and, as with HCl, gases other than HCl may migrate into these gaps.
[0050] The present invention will be described in more detail by the following non-limiting figures and embodiments.
[0051] Figures 1-4, 10, and 12 show enlarged schematic cross-sections of devices for high-temperature applications. Each figure (and, in the case of Figures 1-3, each panel arranged in rows and columns) shows only a portion of the device, which includes a portion of part 2 of the device (shown in black at the bottom of each panel) and a portion of the refractory carbide layer on the surface of part 2.
[0052] For each figure (and in the case of Figures 1-3, each panel arranged in rows and columns), the hatched lines of the refractory carbide layer, drawn parallel to each other from the left of the lower boundary to the right of the upper boundary (for example, the shading shown at the top of Figure 1), indicate a larger average linear section grain size than any directly adjacent refractory carbide layer. The intersection of horizontal and vertical lines (the shading in the middle of Figure 1) indicates a high porosity exceeding that of any directly adjacent refractory carbide layer. Circles (representing layers in the middle column of Figure 2) indicate layers rich in non-carbon components of refractory carbide, containing more non-carbon components of refractory carbide than any directly adjacent refractory carbide layer.
[0053] The device illustrated in the three lower panels of Figure 1 includes a refractory carbide multilayer 10 of the present invention on the surface of part 2. This refractory carbide multilayer 10 includes a first layer 11, a second layer 12, a third layer 13, a fourth layer 14, and a fifth layer 15. It is not apparent from the schematic diagram of Figure 1 that each layer 11, 12, 13, 14, and 15 may have an average thickness far exceeding 25 nm and contains at least one refractory carbide. In this embodiment, the first, third, and fifth layers 11, 13, and 15 have an average linear section grain size greater than that of the second and fourth layers 12 and 14, and the porosity of layers 12 and 14 exceeds that of the first, third, and fifth layers 11, 13, and 15.
[0054] Figure 1 further illustrates the effect of mechanical forces (see upper arrow) and how the multilayer of the present invention helps mitigate crack propagation by refracting cracks along the plane of the layer, thereby reducing the probability that the cracks will reach the substrate. In monolayers containing large refractory carbide crystals (see upper right panel) or monolayers of highly porous refractory carbides (see middle row, right panel), as illustrated in the upper and middle rows and right panel, crack propagation can very easily reach the surface of part 2.
[0055] The device illustrated on the right side of Figure 2 includes a refractory carbide multilayer 10 of the present invention on the surface of part 2. The refractory carbide multilayer 10 comprises a first layer 11, a second layer 12, a third layer 13, a fourth layer 14, and a fifth layer 15. Each layer 11, 12, 13, 14, and 15 has an average thickness well over 25 nm and contains at least one refractory carbide. In this embodiment, the first, third, and fifth layers 11, 13, and 15 have an average linear section grain size greater than that of the second and fourth layers 12 and 14. Layers 12 and 14 differ from the layers 12 and 14 shown in Figure 1. In contrast to the multilayer shown in Figure 1, layers 12 and 14 contain more non-carbon components of refractory carbides than any directly adjacent refractory carbide layer 11, 13, or 15.
[0056] Figure 2 further illustrates the resistance of refractory carbide multilayers to thermal HCl gas, a common etching gas used in semiconductor applications of refractory carbide-coated graphite. The top row shows the initial state of different devices with different layers before etching. The arrows between the top and bottom rows indicate HCl etching. The bottom row illustrates the state of different devices with different layers after etching. It is known that the outer silicon carbide layer with an atomic ratio of Si:C=1 can withstand etching with thermal HCl gas (a common gas used in semiconductor applications of SiC-coated graphite) better than silicon-enhanced SiC. Therefore, having one or more layers of stoichiometric SiC, which typically have larger crystals (or larger mean linear intersection grain size) than adjacent non-stoichiometric layers, is considered to help extend the lifetime. The inventors surprisingly discovered that the lifetime of the refractory carbide layer when exposed to etching gases can be extended by including a layer with low etching resistance (a layer containing more non-carbon components of a similar refractory carbide, e.g., silicon-reinforced SiC). This low etching resistance layer is assumed to act as a sacrificial layer that slows down etching and changes the preferred direction of etching from perpendicular to the surface to parallel. This can be seen in Figure 2, bottom row. In the layer with an atomic ratio of Si:C=1, etching to the graphite surface occurs as expected (see deep etch pits in Figure 2, bottom row left), but the monolayer containing excess silicon has low overall resistance to HCl and disappears due to HCl (see Figure 2, bottom row middle). Surprisingly, the multilayer in the device on the right provides the best etching protection to the coated graphite, as both the expected etching to the graphite surface and the overall rapid disappearance of the (multi)layer are avoided. By adjusting the atomic ratio (e.g., Si:C ratio) in individual layers of a refractory carbide (e.g., silicon carbide) multilayer, it becomes possible to reduce chemical etching in several key applications.
[0057] Figure 3 is a schematic diagram of surface grain size control using the multilayer method of the present invention. The three panels on the left show columnar growth of refractory carbide for a thin layer of refractory carbide obtained after a short CVD coating time (top panel), a slightly thicker layer of refractory carbide obtained after a moderate CVD coating time (center panel), and a thicker layer of refractory carbide obtained after a long CVD coating time (bottom panel). When SiC growth of layer thicknesses as shown in the bottom left panel is performed in a monolithic manner (i.e., without the multilayer method of the present invention), the CVD growth pattern, such as columnar growth, continues in a generally uniform manner, meaning that the width of the crystal column gradually widens as growth continues from the initial nucleation site on the graphite surface. This means that the surface grain size on the surface becomes larger because it is determined by the diameter of the column itself. As a result, the layer thickness affects the surface grain size. However, in applications of refractory carbide (e.g., SiC coated) graphite in semiconductor equipment, such as epitaxy reactors, the morphology of the SiC plays an important role. While some applications require smaller surface grain sizes, larger surface grain sizes are preferred elsewhere. Surface grain size also affects emissivity, and controlling emissivity is often important for controlling radiant energy emission from the surface. Because the multilayer of the present invention can hinder columnar growth, the surface grain size at the surface is primarily determined by the thickness of the outermost intermediate layer. This provides a valuable method for adjusting the surface grain size. The lower right panel shows a portion of the cross-section of the device of the present invention, in which the multilayer includes a first layer 11 and a third layer 13, the mean linear intersection grain size being greater than that of the second layer 12. The mean thickness of the third layer 13, which is the surface layer and determines the surface grain size at the surface, corresponds to the total thickness of the single layer shown in the upper left panel. Nevertheless, the stability against mechanical forces and etching described above with reference to Figures 1 and 2 can be further incorporated by appropriate selection of layer 12. This results in a (multi)layer with unprecedented stability and precisely matched surface grain size at the outer surface.
[0058] In a preferred embodiment of the present invention, the average linear section grain size of at least two layers is smaller than that of the other layers. Referring to Figure 3, the first layer 11 in the lower right panel has a larger average linear section grain size compared to the second layer 12 and the third layer 13. [Examples]
[0059] (Examples 1a, 1b, and 1c) A silicon carbide multilayer in which some silicon carbide layers contain more silicon than others. Purified hydrostatic graphite 2 (less than 5 ppm impurities by mass) was coated with the silicon carbide multilayer 10 of the present invention, which consists of 6 layers: - Innermost silicon-rich silicon carbide layer 12, - A silicon carbide layer 11 containing large silicon carbide crystals, - Silicon-rich silicon carbide layer 13, - A silicon carbide layer containing large silicon carbide crystals, - Silicon-rich silicon carbide layer, and - The outermost silicon carbide layer containing large silicon carbide crystals.
[0060] The expression "contains large silicon carbide crystals" means that the silicon carbide crystals in the silicon-rich layer were smaller. The expression "silicon-rich" means that the silicon content in the layer was higher than that of a silicon carbide layer containing larger refractory carbide crystals.
[0061] During the CVD process, the hydrostatic graphite substrate was heated and exposed to a constant flow rate of hydrogen (H2) and methyltrichlorosilane (MTS) gas under reduced pressure. The MTS underwent a decomposition reaction, generating solid SiC on the substrate surface. The properties of the SiC, particularly the Si content, were adjusted by changing the deposition parameters. The six-layer multilayer structure described above, shown in Figure 4, was deposited on the graphite during a single CVD run by periodically changing the parameters shown in the table below:
[0062] [Table 1]
[0063] During parameter switching, the MTS flow was briefly stopped until the pressure and temperature stabilized. In Example 1a, each of the six layers was deposited within 5 minutes, with a total deposition time of 30 minutes. In Example 1b, the silicon-rich layer was deposited within 2 minutes, with a total deposition time of 21 minutes. In Example 1c, the silicon-rich layer was deposited in just 1 minute, with a total deposition time of just 18 minutes.
[0064] Figure 5 shows a cross-sectional scanning electron microscope (SEM) image of the device of the present invention, including the multilayer formed by Example 1a. Silicon carbide layers containing large silicon carbide crystals appear bright, while silicon-rich silicon carbide layers appear dark. Several crystallites are highlighted in the lower left panel of Figure 5. It is immediately apparent that silicon carbide crystals in layers with larger average linear section grain sizes are indeed larger than those in any of the "silicon-rich silicon carbide layers."
[0065] The layers are sufficiently separated from each other and conform to the structure of the graphite substrate. A multilayer coating structure was observed across the entire substrate surface. Silicon carbide crystals in layers containing large silicon carbide crystals are initially small (less than 1 μm) and become larger as the layer thickness increases (approximately 2-10 μm). Crystallites in silicon-rich layers have a diameter of approximately 0.2-1 μm and do not grow with increasing layer thickness. The silicon-rich layer halts the silicon carbide crystal maturation process and restarts it in the next silicon carbide layer deposited on the outer surface of the silicon-rich layer. Therefore, regardless of the total coating thickness, a silicon-rich intermediate layer can be inserted to adjust the maximum silicon carbide crystal diameter in the layer deposited on that intermediate layer.
[0066] Figure 6 shows SEM images of the multilayer device of the present invention having six layers formed by Example 1a (left SEM image), 1b (center SEM image), and 1c (right SEM image). Even with a smaller thickness of the silicon-rich layer, the crystal ripening process was interrupted, as discussed above.
[0067] A multilayer structure can be defined in several ways, for example, by changing the number and order of layers, or by varying the thickness of the layers through their deposition time.
[0068] The bottom graph in Figure 7 shows the X-ray diffraction (XRD) of a sample coated with a monolayer of silicon carbide containing large silicon carbide crystals. The top graph in Figure 7 shows the X-ray diffraction of a sample coated with a monolayer of silicon-rich silicon carbide. The second, third, and fourth diffraction patterns from the top are for sample 1a, sample 1b, and sample 1c, respectively. All X-ray diffraction patterns in Figure 7 are plotted on a logarithmic y-axis to improve the visibility of low-intensity peaks.
[0069] The presence of elemental crystalline silicon was confirmed in samples containing at least one silicon-rich layer (Figure 7, upper four diffraction patterns showing diffraction peaks characteristic of crystalline silicon at angle 2θ, indicated by black triangles). The diffraction peak at angle 2θ, indicated by black squares, is characteristic of β-SiC. In addition, several diffraction peaks at angle 2θ, indicated by black circles, originate from the graphite substrate.
[0070] The multilayer structures of samples 1a, 1b, and 1c showed diffraction peaks for both β-SiC and crystalline silicon. The relative intensity of the crystalline silicon diffraction peak decreased with decreasing thickness of the silicon-rich layer.
[0071] Energy-dispersive X-ray spectroscopy (EDXS) was used to further confirm that silicon-rich layers (such as those shown in reference numerals 12 and 13 in Figure 4) actually contained more silicon than layers with larger average linear intersection grain sizes (such as the layer shown in reference numeral 11 in Figure 4). EDXS is a spectroscopic technique used in conjunction with a scanning electron microscope (SEM) and can be performed on limited areas of the SEM image, such as cross-sections of multilayer devices. Figure 8 shows an EDXS line scan of a cross-section of an exemplary six-layer multilayer device. The intensities of the Si Kα and C Kα signals were measured along the lines shown on the cross-section of the exemplary six-layer multilayer device. The intensities obtained in counts per second for Si Kα (left axis) and C Kα (right axis) are plotted against the position along the line (μm). The Si signal intensity differs depending on the cross-section, showing three maximum values in the region where the silicon-rich layers are located (solid line). This confirms that these layers actually contained more silicon than layers with larger average linear intersection grain sizes. As expected, the C signal, which is generally weak in EDXS, is strong only on the graphite substrate.
[0072] The etching resistance of an exemplary multilayer containing six layers was investigated by exposure to etching gas (a stream of 80 vol% Ar and 20 vol% hydrogen chloride HCl) at 1300°C and 100 millibars for 3 hours. After etching, the top layer was damaged and partially removed. The silicon-rich silicon carbide layer beneath it was partially etched, while the four layers below it were all intact. No deep etch pits were formed. This is evident from Figure 9, which shows cross-sectional SEM images of the multilayer containing six layers before (left) and after (right) etching in HCl gas at 1300°C. The underlying problem of deep etch pit formation in monolayers of refractory carbides is also illustrated in the SEM image of Figure 9A. Figure 9A shows a single SiC layer deposited on a graphite substrate. This layer contains large crystals. The deep etch pits shown in Figure 9A were observed after exposure to thermal hydrogen chloride gas under the same conditions as described above. Thus, Figures 9 and 9A provide experimental evidence for the effect described above with respect to Figure 2.
[0073] (Example 2) A multilayer silicon carbide structure containing four silicon carbide layers. The number and thickness of individual layers from Examples 1a, 1b, and 1c can be altered by changing the deposition sequence and the deposition time for each layer. By reducing the number of deposition steps from 6 to 4 in Examples 1a, 1b, and 1c, a multilayer containing only four silicon carbide layers was obtained. To double the thickness of the silicon carbide layers containing large silicon carbide crystals, their respective deposition times were doubled. The resulting coating is shown in Figure 10, which includes a schematic diagram in the upper left portion of the figure and an SEM micrograph in the upper right portion. The EDXS line scan shown at the bottom of Figure 10 supports the excess silicon in the silicon-rich layer.
[0074] The 4-layer multilayer of Example 2 was also etched using hot HCl gas, as described above for the 6-layer multilayer. Most of the sample was etched uniformly from the top (compare with the sample before etching in Figure 11, upper right panel and upper left panel). There were some areas where deeper etch pits were formed (Figure 11, center and lower panels). These reached the outer silicon-rich layer and stopped there. This can be mainly explained by the breakdown of the crystal boundary and favorable etching along the silicon-rich layer.
[0075] Crystal boundaries can extend from the outer surface of a layer to the lower surface of the layer in several locations. This is particularly likely to occur in layers containing large columnar refractory carbide crystals. Silicon-rich layers appear to break these boundaries very efficiently. Thus, HCl that penetrates the layer along these boundaries spreads horizontally into the underlying sacrificial silicon-rich layer. This prevents HCl from penetrating deeper into (multi) layers, thus preventing the formation of deep etch pits.
[0076] (Example 3) A silicon carbide multilayer in which the porosity of some silicon carbide layers exceeds that of other silicon carbide layers. A device including the multilayer of Example 3 is illustrated in Figure 12. This device includes the refractory carbide multilayer 10 of the present invention on the surface of part 2. The refractory carbide multilayer 10 includes a first silicon carbide layer 11, a second silicon carbide layer 12, a third silicon carbide layer 13, a fourth silicon carbide layer 14, and a fifth silicon carbide layer 15. The porosity of silicon carbide layers 12 and 14 exceeds that of silicon carbide layers 11, 13, and 15. Layers 11, 13, and 15 have a larger average linear section grain size than layers 12 and 14.
[0077] Such multilayer structures containing alternating layers can be produced by CVD by changing growth parameters during the CVD process. The multilayer structures were deposited on hydrostatic graphite by CVD. Layers 11, 13, and 15 were produced from MTS and H2 gas. The more porous layers 12 and 14 were produced from MTS, C2H4, and H2 gas, and the Si / C molar ratio in this gas phase could be adjusted by the amount of C2H4 added. Growth was not stopped when switching from one layer to another, and only the C2H4 flow was activated / deactivated. The five-layer multilayer structure of Example 3 was deposited on graphite during a single CVD run by periodically changing the parameters shown in the table below:
[0078] [Table 2]
[0079] Figure 13 shows a cross-sectional SEM image of the device according to Example 3. The SEM cross-sectional image (Figure 11) shows the presence of five well-separated layers, three of which are dense and faceted, and two are porous. The layers grew well on top of each other, forming fairly sharp interfaces. During sample preparation (breaking of the coated graphite sample), a portion of the upper layer peeled off (arrow in the upper panel of Figure 13). This indicates that the porous layer has lower toughness, which is likely beneficial for the crack deflection discussed in Figure 1. Differences in elemental composition were not apparent by EDXS. XRD showed only the presence of silicon carbide and graphite, the latter likely originating from the graphite substrate.
[0080] As another example, etching resistance was investigated in HCl gas. The SEM image shows that mainly the upper layer of the coating was etched (Figure 14). When HCl reaches the underlying porous layer, it further etches in a dendritic manner. This appears to be beneficial in refracting and stopping deeper etch pits. Therefore, the effect of the porous layer is similar to the effect discussed above for silicon-rich layers in silicon carbide multilayers.
[0081] (Example 4) Determination of average linear intercept surface grain size For the outer surfaces of different devices including the silicon carbide multilayer of the present invention or the comparative silicon carbide monolayer, the average linear intercept surface grain size was determined based on the definition of "average linear intercept grain size" in ISO 13383-1:2012(EN). In all examples, the outer surfaces from which the average linear intercept surface grain size was derived were deposited under the conditions mentioned in the table above for Examples 1a, 1b, and 1c of the "silicon carbide layer containing large silicon carbide crystals".
[0082] In Figure 15, the average linear intercept surface grain size (vertical axis) is plotted against the total layer thickness (horizontal axis). Data obtained for the comparative silicon carbide monolayer are represented by black circles. In the silicon carbide monolayer, the average linear intercept surface grain size was found to increase with increasing monolayer thickness, as can be seen from the dotted line in Figure 15. Data obtained for the silicon carbide multilayer of the present invention are represented by black triangles (sample from Example 1a), black squares (sample from Example 2), and black rhombuses (sample from Example 3). As indicated by the numbers in parentheses in Figure 15, the outermost layer of one investigated silicon carbide multilayer with a total thickness of approximately 39 μm had an average thickness of 7.5 μm. The outermost layer of another investigated silicon carbide multilayer with a total thickness of approximately 42 μm had an average thickness of 14.8 μm. The outermost layer of a third investigated silicon carbide multilayer with a total thickness of approximately 29 μm had an average thickness of 4.9 μm. As demonstrated by the present invention, when the outermost layer is deposited on a silicon-rich silicon carbide layer or a porous silicon carbide layer, the average linear section particle size is determined by the average thickness of the outermost layer.
[0083] Therefore, according to the present invention, not only can etching resistance and resistance to mechanical forces be increased, but the average linear intercept surface grain size can also be controlled with great precision by selecting the thickness of the outermost layer as needed. Thus, the multilayers and devices of the present invention can be used for long periods in a wide range of different semiconductor applications due to their high resistance, and can be used in applications that require particularly small or large surface grain sizes.
[0084] (Example 5) Determination of porosity in layers with high porosity The porosity of the single-layer coatings deposited under the conditions referred to as “porous layers 12 and 14” in Example 3 was estimated. The coated samples were fractured, and the cross-sections were gently polished, first using a diamond polishing disc, and then using a diamond slurry. The resulting polished cross-sections were examined by SEM, as shown in Figure 16. Here, the regions of the cross-section containing pores can be easily distinguished from the high-density regions by light-dark contrast. Porosity was calculated by measuring the area of the cross-section containing pores and dividing this area by the total area examined. This was done at three locations along the cross-section, and the average porosity and standard deviation were estimated to be 25% ± 4%. [Explanation of Symbols]
[0085] 2C...Graphite 10...Refractory carbide multilayer 11...1st layer 12...2nd layer 13...Third layer 14...4th layer 15...5th layer
Claims
1. A refractory carbide multilayer (10) comprising a first layer (11), a second layer (12), and a third layer (13), The first layer (11) has an average thickness of at least 25 nm and contains at least one type of refractory carbide. The second layer (12) has an average thickness of at least 25 nm and contains at least one type of refractory carbide. The third layer (13) has an average thickness of at least 25 nm and contains at least one type of refractory carbide. The first layer (11) has a larger average linear intercept cross-sectional grain size than the second layer (12). The second layer (12) is sandwiched between the first layer (11) and the third layer (13). The average linear section grain size of the third layer (13) is larger than that of the second layer (12). The multilayer (10) wherein the average linear intercept surface grain size of the outer surface of the multilayer (10) is in the range of 0.1 to 50 μm, where the average linear intercept surface grain size is determined relative to the outer surface based on the definition of "average linear intercept grain size" in ISO 13383-1:2012(EN).
2. The multilayer according to claim 1, wherein at least one refractory carbide of at least one layer comprises silicon carbide, tantalum carbide, niobium carbide, hafnium carbide, tungsten carbide, boron carbide, niobium tantalum carbide, hafnium tantalum carbide, or hafnium niobium carbide.
3. The multilayer (10) according to claim 1, wherein the second layer (12) contains more non-carbon components of refractory carbide than the first layer (11).
4. The multilayer (10) according to claim 1, wherein the porosity of the second layer (12) exceeds the porosity of the first layer (11).
5. - The average thickness of all individual layers is in the range of 0.1 μm to 100 mm for all layers of the independent multilayer (10) structure. The multilayer (10) according to claim 1.
6. Use of the multilayer (10) according to claim 1 as a coating for a support to extend the life of the support in an etching gas-containing atmosphere and / or when exposed to mechanical stress.
Citation Information
Patent Citations
SiC product and manufacturing method thereof
EP0935013A1
Process for manufacturing a silicon carbide coated body
EP3514130A1
Treatment member for semiconductor use
JP1993006862A
Heat treatment jig and its manufacture
JP1995335728A
Multilayer silicon carbide wafer
JP1999121315A